A bioinformatics analysis of the correlation between hepatic ischemia–reperfusion injury and postoperative cognitive dysfunction - Hu, Qing; Liu, Haijie; Bao, Yunfei; Feng, Zhihao; Zhang, Hongbo; Li, Jianling (Frontiers in Genetics, 2025)
BackgroundPostoperative cognitive dysfunction (POCD) is a common postoperative complication that is prevalent in elderly people. An increasing number of elderly patients are undergoing surgery. As a result, the number of patients presenting with POCD is increasing. Previous studies have demonstrated that hepatic ischemia–reperfusion injury (HIRI) in mice is associated with postoperative cognitive impairment. Therefore, this study investigated the relationship between POCD and HIRI using bioinformatics research methods.MethodsThe Gene Expression Omnibus (GEO) database GSE202565 and GeneCards data were selected for correlation analysis using bioinformatics analysis methods. The GSE112713 dataset from the GEO database was chosen for preliminary validation of the screened hub genes.ResultsWe analyzed the dataset GSE202565 for differences in gene expression before and after hepatic post-ischemic reperfusion and obtained a total of 53 genes by identifying POCD-related genes. We also screened these 53 genes again and obtained 10 hub genes, which were analyzed and used for correlation prediction. Finally, these 10 hub genes were partially and preliminarily validated using the dataset GSE112713.ConclusionHIRI is closely related to POCD, and reducing the occurrence of HIRI may become one of the ways to avoid or improve postoperative cognitive impairment in the future.